2017
DOI: 10.1038/srep43251
|View full text |Cite
|
Sign up to set email alerts
|

UVRAG Deficiency Exacerbates Doxorubicin-Induced Cardiotoxicity

Abstract: Doxorubicin (DOX) is an effective chemotherapeutic drug in the treatment of various types of cancers. However, its clinical application has been largely limited by potential development of cardiotoxicity. Previously we have shown that ultra-violet radiation resistance-associated gene (UVRAG), an autophagy-related protein, is essential for the maintenance of autophagic flux in the heart under physiological conditions. Here, we sought to determine the role of UVRAG-mediated autophagy in DOX-induced cardiotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Furthermore, the authors studies tissue-specific loss-of-function models of ATG7, a protein critical for autophagosome formation, and demonstrate the critical need for autophagy signaling in individual tissues for the specific benefits. Intermittent fasting has also been demonstrated to prevent doxorubicin-induced cardiomyopathy in a mouse model of repetitive doxycycline exposure resulting in cardiomyopathy (7). Intermittent fasting rescued the impaired autophagic flux in this setting, which was worsened by concomitant deficiency of UVRAG, a protein essential for autophagosome formation.…”
Section: Benefits Of Intermittent Fasting In Animal Models On Cardiommentioning
confidence: 99%
“…Furthermore, the authors studies tissue-specific loss-of-function models of ATG7, a protein critical for autophagosome formation, and demonstrate the critical need for autophagy signaling in individual tissues for the specific benefits. Intermittent fasting has also been demonstrated to prevent doxorubicin-induced cardiomyopathy in a mouse model of repetitive doxycycline exposure resulting in cardiomyopathy (7). Intermittent fasting rescued the impaired autophagic flux in this setting, which was worsened by concomitant deficiency of UVRAG, a protein essential for autophagosome formation.…”
Section: Benefits Of Intermittent Fasting In Animal Models On Cardiommentioning
confidence: 99%
“…We and others have recently shown that autophagic flux is impaired in the mouse models of doxorubicin-induced cardiotoxicity, which contributes to heart injury [14][15][16]. Moreover, we have shown that IF is capable of restoring autophagic flux and ameliorating pathological alterations including increased cytoplasmic vacuolization, fibrosis, apoptosis and generation of reactive oxygen species in both acute and chronic doxorubicin cardiotoxicity [16]. Thus, IF could serve as a promising strategy for the prevention and control of doxorubicininduced cardiotoxicity.…”
Section: If and Doxorubicin-induced Cardiotoxicitymentioning
confidence: 79%
“…The discrepancies may be caused by the difference in animal species, cell types, methods monitoring autophagy, means of drug administration, and dosage and duration of the drug used in these studies. More recently, we and others have shown that DOX treatment stimulated autophagy initiation, while suppressed multiple subsequent steps including autophagosome formation, autophagosome maturation and lysosomal degradation [7,27,29,30]. As a consequence, the autophagic flux was attenuated in DOX-induced cardiotoxicity.…”
Section: Macroautophagy Dysregulationmentioning
confidence: 81%
“…However, it is controversial whether autophagy is activated or suppressed. There are studies showing that DOX treatment activates autophagy in the heart or cardiomyocytes [23][24][25][26], while others have shown conflicting results [7,[27][28][29][30]. Moreover, the significance of autophagy in DOX cardiotoxicity is still on debate.…”
Section: Macroautophagy Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation